What Do You Know About Fiber? - Jennifer Hillan; Claudia Peñuela (EDIS)
Revised! FCS8689, a 3-page fact sheet by Jennifer Hillan and Claudia Peñuela, answers basic questions about fiber. Includes references. Published by the UF Department of Family, Youth and Community Sciences, October 2010.